2015
DOI: 10.1128/jcm.00607-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo IS 6110 Profile Changes in a Mycobacterium tuberculosis Strain as Determined by Tracking over 14 Years

Abstract: f Transposition and homologous recombination of IS6110 appear in Mycobacterium tuberculosis along in vivo sequential infections. These events were checked in different clones of a successful strain, M. tuberculosis Zaragoza, with the focus on a variant in which integration of a copy of IS6110 in the origin of replication (oriC) region occurred. Clonal Mycobacterium tuberculosis variants appear along the sequential infections of hosts involved in the same transmission cluster (1). IS6110 in M. tuberculosis has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…More than a thousand cases infected by this single strain have been identified during the last 23 years 17 . Similar findings were reported in Zaragoza, Spain, where a strain progressed from being low-prevalence to responsible for around 20% of the all tuberculosis cases in the population, with high rates maintained throughout the period 18 .…”
Section: Discussionsupporting
confidence: 86%
“…More than a thousand cases infected by this single strain have been identified during the last 23 years 17 . Similar findings were reported in Zaragoza, Spain, where a strain progressed from being low-prevalence to responsible for around 20% of the all tuberculosis cases in the population, with high rates maintained throughout the period 18 .…”
Section: Discussionsupporting
confidence: 86%
“…In addition, it shared the five locations of the IS6110 with Ara50. Modifications in the RFLP pattern were observed before for strains belonging to the same cluster [19,20]. In contrast, three of these isolates were not related to the Ara50 outbreak.…”
Section: Discussionmentioning
confidence: 65%
“…Diverse epidemiological studies have demonstrated that IS 6110 RFLP presents distinct profiles in M . tuberculosis transmission clusters [ 28 , 64 67 ]. Since these studies involve isolates from different patients isolated during prolonged periods of time, it is plausible to think that IS 6110 -mediated adaptive mechanisms might be involved in the patient-to-patient transmission of M .…”
Section: Discussionmentioning
confidence: 99%
“…This confers plasticity to the MTBC genomes and could have significant biological implications. As for other IS, insertion of IS 6110 into a coding region frequently renders the gene inactive, the basis of transposon mutagenesis, or the recombination between two IS 6110 copies can lead to either inversion or deletion of the chromosomal fragment between them [ 26 28 ]. Furthermore, it has been demonstrated that IS 6110 acts as a mobile promoter and this phenotype is selectively activated during in vitro infection of monocytes/macrophages [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%